Genetic diversity and differentiation of cultured Nile tilapia populations from Ethiopia revealed by ddRAD-seq: implications for better hatchery management - Geletu Temesgen Tola; Tang Shoujie; Zhao Jinliang (Aquatic Living Resources)
Sub-Saharan Africa, including Ethiopia, is a center of native Nile tilapia populations, which are important for conservation and aquaculture development. Nile tilapia aquaculture in Ethiopia is dominated by small-scale fish farming in ponds, with seeds from poorly managed hatcheries and wild sources. Hence, the development of aquaculture in Ethiopia faces a major hurdle owing to the absence of good-quality seeds, largely because of the lack of genetic management practices within hatchery centers. This study aimed to assess the genetic diversity and differentiation among farmed Nile tilapia populations to inform genetic management strategies and support the development of robust strains for aquaculture advancement. Using ddRAD-seq technology for SNP discovery, we assessed genetic diversity metrics across three farmed populations, Sebeta, Batu, and Aweday, comprising 20, 21, and 15 individuals, respectively. Expected heterozyosity (He), observed heterozygosity (Ho) and nucleotide diversity (π) estimates indicated moderate within-population genetic diversity (mean: He = 0.24, Ho = 0.25, π = 0.25). Pairwise FST values revealed the highest genetic distance (FST = 0.067) between Batu and Aweday populations, while the lowest genetic distance (FST = 0.027) was observed between Sebeta and Aweday populations. STRUCTURE analysis identified two genetic clusters, with the first cluster including Batu individuals and some from Sebeta and Aweday. Overall, our results show moderate within-population genetic variation and weak genetic differentiation among the populations. This study underscores the importance of documentation of broodstock backgrounds and formulation of reasonable hatchery practices to assist in aquaculture development and conservation of native genetic resources in Ethiopia.